EXFOLIATIVE VAGINAL CYTOLOGY, VAGINAL pH AND VAGINAL ELECTRICAL RESISTANCE IN SPONTANEOUS AND INDUCED ESTRUS: A COMPARATIVE STUDY TO PREDICT FERTILITY IN BITCHES - Jayasudha, B; RAJU, K.G.Solmon; Reddy, K C S; Nagaraj, P (The Indian Journal of Animal Reproduction, 2020)
A total of 18 anestrus bitches were randomly divided into 3 groups (G-I, G-II and G-III) and 6 cyclic bitches were considered as G-IV. Estrus was induced in G-I and G-II groups with Cabergoline @ 5 μg per kg body weight orally till the second day of proestrual bleeding and eCG + hCG @ 20 IU/Kg b.wt for 6 days with single injection of hCG @ 500 IU per bitch on day 7, respectively. G-III (anestrus control) bitches were treated with normal saline for 7days and G IV (estrus control) bitches were allowed to exhibit estrus spontaneously. In the present study, vaginal exfoliative cytology along with VER at estrus was recommended to predict best fertility among induced with cabergoline and cyclical estrus exhibited bitches.